Influence Of Management Information Systems, Human Resource Management, And Regional Leadership On Effectiveness Of E-Government Implementation In Ciamis Regency - Irfan Nursetiawan (International Journal Labs, 2025)
The implementation of e-Government in the regions still faces obstacles, especially related to the readiness of management information systems, the quality of human resources, and leadership capacity in directing change. This study aims to analyze the influence of Management Information Systems, Human Resource Management, and Leadership on the implementation of e-Government by using quantitative research methods and multiple linear regression analysis. The results of the study showed that the Management Information System and Human Resource Management did not have a significant influence on the implementation of e-Government, while the Leadership variable was proven to have a significant effect with a significance value of 0.003. These findings indicate that the success of e-Government is more determined by leadership that is able to influence the direction of the organization, build a digital culture, and make strategic decisions oriented towards the transformation of public services. The novelty of this research lies in strengthening the perspective of digital leadership in the government sector, namely how leadership capacity plays a key factor in encouraging the adoption and sustainability of e-Government, beyond the role of technology and human resources. Based on these results, it is suggested that the Regional Government, especially Ciamis Regency, strengthen digital leadership through technology-based leadership training and increased leadership involvement in the government's digital transformation process.